The effect of insulating barriers on AC breakdown voltage in inhomogeneous field - Kara, A.; Onal, E.; Kalenderli, O.; Mardikyan, K. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
In this study, the effect of insulating barriers on the breakdown voltage of air in inhomogeneous field is observed. Tests are conducted in order to measure the 50 Hz AC breakdown voltage of small air gaps (up to 50 mm) formed by hemispherically capped rod-plane electrodes with an insulating barrier between them. Energized rod and grounded plane gaps are studied with the flat insulating barriers that have three different diameters. The results of the test series show how the breakdown voltage varies with the distance between the electrodes, the size and the material of the barrier, the relative position of the electrodes and the barrier between them. As a result, all three materials show nearly same effect when they are used as a barrier, the breakdown voltage varies due to the size of the barriers and the maximum flashover voltages are observed when the barriers are positioned at the nearest point to the rod electrode and the small sized barriers become effective only in very small air gaps